Person-centred counselling psychology : an introduction - Gillon, Ewan (London : SAGE, 2007)
Presents an introduction to the philosophy, theory and practice of the person-centred approach. This book shows how the person-centred approach relates to others within counselling psychology and to contemporary practices in mental health generally
Includes bibliographical references (p. [190]-205) and index
PSYCH
Keywords: Client-centered psychotherapy